Alarmins, COVID-19 and comorbidities. (1st January 2021) - Di Salvo, Eleonora; Di Gioacchino, Mario; Tonacci, Alessandro; Casciaro, Marco; Gangemi, Sebastiano
Abstract: The coronavirus SARS-CoV-2, the aetiological agent of COVID-19 disease, is representing a worldwide threat for the medical community and the society at large so that it is being defined as "the twenty-first-century disease". Often associated with a severe cytokine storm, leading to more severe cases, it is mandatory to block such occurrence early in the disease course, to prevent the patients from having more severe, sometimes fatal, outcomes. In this framework, early detection of "danger signals", possibly represented by alarmins, can represent one of the most promising strategies to effectively tailor the disease and to better understand the underlying mechanisms eventually leading to death or severe consequences. In light of such considerations, the present article aims at evaluating the role of alarmins in patients affected by COVID-19 disease and the relationship of such compounds with the most commonly reported comorbidities. The conducted researches demonstrated yet poor literature on this specific topic, however preliminarily confirming a role for danger signals in the amplification of the inflammatory reaction associated with SARS-CoV-2 infection. As such, a number of chronic conditions, including metabolic syndrome, gastrointestinal and respiratory diseases, in turn, associated with higher levels of alarmins, both foster the infection and predispose to a worse prognosis. According to these preliminary data, prompt detection of high levels of alarmins in patients with COVID-19 and co-morbidities could suggest an immediate intense anti-inflammatory treatment. Key message: Alarmins have a role in the amplification of the inflammatory reaction associated with SARS-CoV-2 infection a prompt detection of high levels of alarmins in patients with COVID-19 could suggest an immediate intense anti-inflammatory treatment